(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Management of severe pre eclampsia remote from term remains one of the most difficult challenges in obstetric practice. Expectant management of early onset severe pre eclampsia improves neonatal outcome. Methods: A prospective case series extending over five years peiod were recorded to evaluate the maternal and perinatal outcome of expectant management of severe preeclampsia presenting between 24-34 weeks of gestation in a tertiary referral center. All women (n=160) presenting with early onset (24-34 weeks of gestation) severe preeclampsia , where both the mother and the fetus were otherwise stable. Frequent clinical and biochemical monitoring of maternal status with careful blood pressure control. Foetal surveillance included six hourly foetal heart rate monitoring, bi weekly non stress test and weekly USG evaluation. Results: Mean number of days of prolongation of gestation was 6 days ( range 1-24days). The largest prolongation of pregnancy was recorded in patients with the lowest gestational age. Conservative management was associated with a 1.63% ( 17/160) intrauterine fetal loss rate. The days of pregnancy prolongation and perinatal mortality were significantly higher among those managed at <30 weeks. Increasing gestational age correlated with a reduction of RDS ( respiratory distress syndrome). Maternal morbidities were significantly higher among those managed at < 32 weeks. But there was no maternal mortality. Conclusion: Good perinatal outcome and less risk to mother can be achieved at 30-34 weeks gestation. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 73-78